Perbandingan Pengaruh Konsumsi Jus Terong Belanda Segar dan Komersil Terhadap Tikus Obesitas - Syahputra, Hariyadi Dharmawan; Harahap, Daimah Wirdatus Sanaun; Iksen, Iksen; Gurning, Kasta (Herbal Medicine Journal, 2025)
Background: High yield carbohydrate diet is common in Indonesia mainly in North Sumatra province. In the long run consuming primary carbohydrate form rice may increase the risk for diabetic and its complication. Not only the amount of rice but certain beverages also such as tamarillo juice, though it’s rich amount of nutritious benefit, some product may yield more sugar to improve from its sour or bitter flavor. Objectives: studies aim to find the diet correlation between amount of carbohydrate total and Vitamin C intake in fresh and store brought tamarillo juice affect animal model with high sucrose induction. Material and Methods: Fresh tamarillo fruit grew in north Sumatra blended versus store brought juice are given daily towards obese female rats induced with 2 ml of lard and 5% sucrose orally for five weeks. Beforehand sample had its total carbohydrate and Vitamin C content with iodometric method. The last 2 weeks then rats treated with fresh blend and store brought product juice. Results: Total content value obtained from fresh compared with store brought tamarillo juice in vitamin C, (18.63 ± 7.16 mg/ml); (11.57 ± 6.8 mg/ml) and total carbohydrate (15.02 ± 2.35 mg/ml); (25.37 ± 28.17 mg/ml) respectively. During treatment increase in body weight significantly in store brought product. Histology remarks in pancreas do not show any significance damage in cell especially for fresh blend treatment group. Conclusion: Fresh blend tamarillo juice may improve health and can be considered safe for subject that like to consume high carbs in their diet.